The Use of Arteriovenous Bundle Interposition Grafts in Microsurgical Reconstruction: A Systematic Review of the Literature - Kareh, Aurora M.; Tadisina, Kashyap Komarraju; Chun, Magnus; Kaswan, Sumesh; Xu, Kyle Y. (Archives of Plastic Surgery, 2022)
Microvascular reconstruction frequently requires anastomosis outside of the zone of injury for successful reconstruction. Multiple options exist for pedicle lengthening including vein grafts, arteriovenous loops, and arteriovenous bundle interposition grafts. The authors performed a systematic review of arteriovenous bundle interposition grafts to elucidate indications and outcomes of arteriovenous grafts in microvascular reconstruction. A systematic review of the literature was performed using targeted keywords. Data extraction was performed by two independent authors, and descriptive statistics were used to analyze pooled data. Forty-four patients underwent pedicle lengthening with an arteriovenous graft from the descending branch of the lateral circumflex femoral artery. Most common indications for flap reconstruction were malignancy (n = 12), trauma (n = 7), and diabetic ulceration (n = 4). The most commonly used free flap was the anterolateral thigh flap (n = 18). There were five complications, with one resulting in flap loss. Arteriovenous bundle interposition grafts are a viable option for pedicle lengthening when free flap distant anastomosis is required. The descending branch of the lateral circumflex femoral artery may be used for a variety of defects and can be used in conjunction with fasciocutaneous, osteocutaneous, muscle, and chimeric free flaps.
Keywords: arteriovenous bundle interposition grafts; pedicle lengthening; arteriovenous loop; arteriovenous grafts